SIED-GISCOR recommendations for colonoscopy in screening programs: Part I – Diagnostic - Parodi, Maria Caterina; Antonelli, Giulio; Galloro, Giuseppe; Radaelli, Franco; Manes, Giampiero; Manno, Mauro; Camellini, Lorenzo; Sereni, Giuliana; Caserta, Luigi; Arrigoni, Arrigo; Fasoli, Renato; Sassatelli, Romano; et al. (Digestive and liver disease, 2024)
The implementation of FIT programs reduces incidence and mortality from CRC in the screened subjects. The ultimate efficacy for CRC morbidity and mortality prevention in a FIT program depends on the colonoscopy in FIT+ subjects that has the task of detecting and removing these advanced lesions. Recently, there has been growing evidence on factors that influence the quality of colonoscopy specifically withing organized FIT programs, prompting to dedicated interventions in order to maximize the benefit/harm ratio of post-FIT colonoscopy. This document focuses on the diagnostic phase of colonoscopy, providing indications on how to standardise colonoscopy in FIT+ subjects, regarding timing of examination, management of antithrombotic therapy, bowel preparation, competence and sedation.